Exploring the role of people providing informal support to survivors of domestic abuse during the COVID-19 pandemic: a qualitative study. (November 2021) - Gregory, Alison; Williamson, Emma
Abstract: Background: The COVID-19 pandemic intensified women's experiences of domestic abuse. Demand for specialist support increased substantially, and UK campaigns encouraged friends, family members, neighbours, and colleagues of domestic abuse survivors to provide support informally. Research with informal supporter participants is rare, and yet, they are likely to have a good knowledge of the situation and to have substantial influence on outcomes. The aim of this research was to investigate how the pandemic impacted on informal supporters' appraisals of abusive situations and on their ability to provide assistance. Methods: A qualitative study with informal supporters of female domestic abuse survivors was underway at the start of the COVID-19 pandemic. Participants were recruited in the Southwest of England using advertisements in community venues and, once social distancing and lockdown measures were introduced, recruitment was extended across England using social media advertisements. We added additional questions about the impact of the pandemic and the related social restrictions to the topic guide. 18 in-depth semi-structured interviews were conducted with three male and 15 female informal supporters (aged 25–69 years), over the telephone and using Skype. All participants gave recorded, oral informed consent. A secondary analysis of data relating specifically to the pandemic was undertaken using reflexive thematic analysis. The original study, and subsequent amendments, were granted ethics approval by the Research Ethics Committee in the School for Policy Studies at the University of Bristol. Findings: The subset of participant interviews reported in this paper were held between March 30, 2020, and Sept 15, 2020. The themes generated in the analysis indicated four main findings. First, it seemed that the pandemic changed people's ability to "read" situations and to accurately assess the level of risk. Informal supporters felt greater uncertainty about whether the abuse had continued, altered, or escalated. Second, perpetrators' tactics evolved to further abuse by exploiting the pandemic. In particular, they increased surveillance and capitalised on reduced in-person contact. Third, the pandemic created a context where the capacity of informal supporters was increasingly stretched, and where safely offering support became more challenging. Finally, informal supporters demonstrated resourcefulness and creativity, for example, by forming support bubbles with survivors and finding novel ways to monitor the situation, in order to continue offering help. Interpretation: In the face of uncertainty, and an incredibly challenging life-context, informal supporters of domestic abuse survivors demonstrated resilience, creativity, and innovation as they continued to offer support. The pandemic has simultaneously highlighted the importance of informal support, and the challenges in providing it. More direct research with informal supporters is crucial to determine how best to support and equip this population. Funding: AXA Research Fund.